How did the authors of the Breviarium Alaricanum work? The example of the laws on Jews. - Nemo‐Pekelman, Capucine (Historical Research, 2013)
To understand the authors of the Breviarium Alaricanum (a law code collected in sixth-century Aquitaine) - their purpose, their logic and their methods - it is necessary to undertake an internal study of the work itself. Thus, this article will analyse the code, focusing on those laws that concern the Jews. In their selection of the sources of Roman law, and the organization of those laws in the Breviary, the 'prudentes' who produced it made significant choices. This is even more apparent in the rewriting and commentaries. These laws reflect the issues which existed in western Jewish communities at that time - issues which, as the compilers knew, were still dealt with in tribunals.